Oppositely charged proteins lead to different effects on the bioaccumulation kinetics of polystyrene nanoplastics in zebrafish (Danio rerio) - Guoliang Zhang; Bowen Xiao; Tao Jiang; Tong Zhao; Jinhui Sun; Huamin Liu; Lixin Wang (Ecotoxicology and Environmental Safety)
Nanoplastics (NPs) are ubiquitous in the natural aquatic environment, thus there is a major need to understand their potential health risk toward aquatic organisms. Proteins are widely spread in the water environment, they may interact with NPs and significantly impact the ecotoxicology of NPs in vivo. In this study, positively charged lysozyme (LYZ) and negatively charged ovalbumin (OVA) were selected as model proteins, and their effects on the bioaccumulation kinetics of polystyrene nanoplastics (PS-NPs) in zebrafish were investigated quantitatively using a biokinetic model. The adsorption of OVA decreased the uptake rates of PS-NPs, thereby reducing the bioconcentration factors (BCF) of PS-NPs in zebrafish. However, in the presence of LYZ, the uptake rates of PS-NPs increased while the depuration rates decreased significantly, as a consequence, the BCF of PS-NPs in zebrafish were elevated. Dynamic light scattering, transmission electron microscopy, and confocal laser scanning microscopy analysis demonstrated that the adsorption of OVA significantly increased the negative charge and hydrodynamic size of PS-NPs, inhibited the interaction between the nanoparticles and negatively charged cell membrane, thus leading to the alleviated bioaccumulation. In contrast, LYZ changed the surface charge of PS-NPs to positive, enhanced the electrostatic attraction and interaction between PS-NPs and cell membrane, thereby increasing the bioavailability of PS-NPs. Our results highlight the impacts of proteins on the biokinetics of NPs, providing novel insights into the ecological risk of nanoplastics.